THE IMPORTANCE OF CLINICAL LABORATORY DIAGNOSTICS IN THE DIAGNOSIS OF UNCOMPLICATED PYELONEPHRITIS (World Bulletin of Public Health, 2026)
Urinary tract infections (UTIs) are among the most common infectious diseases encountered in general medical practice, and 80% of them are classified as uncomplicated urinary tract infections. According to current clinical guidelines, the use of antibiotics is considered the first-line therapeutic option in the treatment of the acute phase of UTIs [1]. This study evaluated routine laboratory parameters—including urinalysis, hematological indices, biochemical markers, and coagulation profiles—in 63 patients diagnosed with uncomplicated pyelonephritis, stratified into four age–sex groups. Urinalysis revealed mild leukocyturia in all patients, consistent with lower urinary tract inflammation. Low-level urinary protein (0.033–0.33 g/L) was detected in a proportion of patients across all groups, while renal epithelial cells were not observed in any case, indicating preserved renal parenchymal integrity. Squamous epithelial cells were more common in women, reflecting physiological anatomical differences. Biochemical parameters (ALT, glucose, urea, creatinine, and total protein) remained within normal reference ranges, with no statistically significant intergroup differences (p > 0.05). Hematological evaluation demonstrated reduced hemoglobin and erythrocyte levels in all groups, with significant intergroup variation in hemoglobin concentration (p = 0.006). ESR was mildly elevated and showed statistically significant differences between specific subgroups (p = 0.0023), whereas leukocyte counts remained within normal limits. Coagulation parameters—including prothrombin time, INR, APTT, thrombin time, and fibrinogen—were within physiological ranges, and no significant differences were present between the groups (all p > 0.05). These findings demonstrate that uncomplicated pyelonephritis is associated with minimal systemic laboratory abnormalities. Mild leukocyturia and lowgrade proteinuria represent the most consistent urinary findings, while the absence of renal epithelial cells confirms the non-complicated nature of the infection. Routine laboratory diagnostics therefore remain essential for accurately distinguishing uncomplicated pyelonephritis from more severe renal or systemic infectious processes.